Religious Moderation in Educational Practice and the Construction of Tolerant Attitudes - Muhammad Muttaqin Alwi; Satria Darma; Agus Purwowidodo; Muh. Nurul Huda (IAIN Manado, 2025)
Religious moderation is a middle way in the sense of being balanced in addressing both issues of religious teachings and responding to phenomena, or acknowledging the reality that occurs. MTsN 2 Blitar Regency is one of the leading madrasahs in Blitar Regency that is proactive in carrying out the ideas of the Ministry of Religious Affairs. The implementation of religious moderation in MTsN 2 Blitar Regency began in the 2023/2024 school year, making it a hot topic among residents in MTsN 2 Blitar Regency. This research is qualitative and was conducted at MTsN 2 Blitar, which is known for its warm implementation of religious moderation. The data in this study were collected using three techniques: in-depth interviews, observation, and documentation. To analyze the data, the researcher employed data condensation techniques, data collection, data display, and verification to conclude. At the same time, the validity of the data was detected by triangulation and peer discussions. The results of the study (1) Planning religious moderation in SKI learning at MTsN 2 Blitar in planning the value of religious moderation are inserted in the teaching module as the first step of religious moderation-based learning. (2) The implementation is the application of the teaching module. Meanwhile, the evaluation includes two types of assessments: formative and summative assessments. (3) The positive impact of the implementation of religious moderation-based learning on SKI subjects in MTsN 2 Blitar increases the competence of educators and education staff, increases knowledge and insight, and fosters a moderate attitude when respecting differences. At the same time, the negative impact felt is the increase in learning materials and methods used by teachers who are perceived as boring